Profile of Cabozantinib for the Treatment of Hepatocellular Carcinoma: Patient Selection and Special Considerations - Debaillon Vesque A; Decraecker M; Blanc JF (Journal of Hepatocellular Carcinoma, 2020)
Audrey Debaillon Vesque,1 Marie Decraecker,1 Jean-Frédéric Blanc1,2 1Department of Oncology, CHU Bordeaux, Hospital Haut Leveque, Pessac 33604 France; 2INSERM U1053, BaRITOn, University Victor Segalen, Bordeaux, FranceCorrespondence: Jean-Frédéric Blanc Email jean-frederic.blanc@chu-bordeaux.frAbstract: Management of advanced hepatocellular carcinoma is challenging. With an increasing number of options for the first and second-line treatment, understanding and developing optimal systemic treatment strategies are crucial. In second line, two tyrosine kinase inhibitors (TKI) and one monoclonal antibody have been approved after sorafenib by both the European Medicines Agency and the Food and Drug Administration based on the results of phase 3 trials: cabozantinib, regorafenib and ramucirumab. Cabozantinib has demonstrated an improved overall survival and progression-free survival in the phase 3 CELESTIAL study in second and third line, in patients in good general condition (performance status 0– 1) and with a normal liver function Child-Pugh class A. Analysis of subgroups has shown that even elderly patients over 65 years, or patients with high baseline alpha-fetoprotein ≥ 400 ng/mL benefit from cabozantinib. The choice in second-line between the three drugs should be based on factors such as previous tolerance of sorafenib, safety profile of drugs and quality of life. In this review, we will analyze clinical data available on cabozantinib, clarifying the choice between the different possible treatments. However, the upcoming of a new standard in first line with the combination atezolizumab and bevacizumab will change the game and will warrant further investigations to define the accurate subsequent sequence of TKIs. Cabozantinib is also actually tested in first-line in combination with atezolizumab, results of the phase 3 COSMIC trial are eagerly awaited.Keywords: advanced hepatocellular carcinoma, cabozantinib, MET, alpha-fetoprotein, AFP, tyrosine kinase inhibitor